Relative captures of grape root borer, Vitacea polistiformis (Lepidoptera: Sesiidae) in pheromone traps within vineyards and adjacent woodlands. (March 2018) - Liburd, Oscar E.; Razze, Janine M.; Nyoike, Teresia W.
Abstract: The grape root borer (GRB), Vitacea polistiformis (Harris), is a significant pest of grapes ( Vitis spp.) throughout parts of the eastern United States. Early detection and implementation of management tactics can prevent economic losses and vine death. The establishment of an effective monitoring program requires the deployment of pheromone baited traps in vineyards and native wild grapes. An understanding of the spatial distribution of GRB infestations is critical for the development of sampling plans and for implementing management decisions. Wing traps baited with synthetic GRB sex pheromones (99:1 blend of (E, Z)-2, 13-ODDA and Z, Z-3, 13-ODDA) were deployed in commercial vineyards and surrounding woodlands in wild grapes to monitor GRB abundance and distribution. In addition, pheromone-baited wing traps were placed at low, medium, and high positions (0.5 m–2 m above the ground) on the grapevine trellis in commercial vineyards to evaluate the effect of trap height on the number of GRB captured. Traps placed in the cultivated vineyard had consistently higher counts of GRB compared with traps along the vineyard edge and in the wild grapes in the woodland. The pheromone-baited traps placed on the highest trellis wire caught more GRB adults than traps placed at the lowest position on the bottom trellis wire. Therefore, we recommend to place traps at approximately 2 m in the upper grapevine canopy early in the season before flight of GRB moth begins in order to aid in the timing and implementation of management tactics. Highlights: Traps in vineyards had more GRB than traps in the vineyard edge and wooded area. Trap height is an important factor in optimizing GRB monitoring efficiency. Deploy 2–4 pheromone-baited traps per hectare on a vineyard to monitor for GRB. In northern Florida, set traps by mid-June for early detection of male GRB moths.